Retrograde Pyelogram during intended Cystogram: A Rare complication of a common procedure - Rajaian, Shanmugasundaram (J Clin Imaging Sci, 2018)
Inadvertent placement of the urinary catheter into the ureter can cause several complications. We describe a rare complication during cystogram due to unrecognized inadvertently placed urinary catheter in ureter, resulting in a life-threatening situation. A 47-year-old multiparous female underwent total laparoscopic hysterectomy for adenomyosis. During early postoperative period, she developed vesicovaginal fistula and transvaginal repair of fistula was done. During filling cystography done at 2 weeks, she developed right loin pain and urosepsis. Contrast extravasation was seen in the right renal subcapsular space with Foley's catheter inside the right ureter. Subsequently, she recovered well.